Experimental study of metal nanoparticle synthesis by an arc evaporation/condensation process - Förster, Henning; Wolfrum, Christian; Peukert, Wolfgang (Journal of Nanoparticle Research, 2012)
The generation of copper nanoparticles in an arc furnace by the evaporation/condensation method is systematically investigated. The evaporation/condensation process is advantageous because it allows direct synthesis using pure metals as starting materials avoiding reactions of expensive and potentially poisonous precursors. In the presented system, a transferred direct current arc provides the energy for evaporation of the metal target. In order to prevent an oxidation of the particles in the process, the synthesis is conducted in an atmosphere of inert gases (purity grade 5.0). The arc stability and its effect on particle synthesis are investigated. The experiments reveal excellent long-term arc stability for at least 8 h continuous operation delivering aerosols with high reproducibility (+/- 10% of average particle size). The influences of the arc current and length, the flow rates of the applied gases and the injection of hydrogen in the plasma zone on the particle size distributions and the agglomerate structure are studied. The produced copper nanoparticles are characterized by scanning mobility particle sizing and scanning electron microscopy. The average particle size could be well controlled in a size range 4-50 nm by selecting appropriate operating parameters.
Keywords: Metal nanoparticles; Synthesis; Arc evaporation/condensation; Aerosol